2018
DOI: 10.1016/j.jcjo.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Retinal thickness measurements in sickle cell patients with HbSS and HbSC genotype

Abstract: ObjectiveTemporal macula thinning has been reported in sickle cell patients, but it remains unclear if there is a difference between HbSS and HbSC genotypes. We aimed to quantitatively compare macular thickness between eyes with HbSS and HbSC genotype.DesignRetrospective descriptive study.MethodsConsecutive patients seen over a 5.5-year period in the Ophthalmology Department at St Thomas’ Hospital, London, were identified. Macular optical coherence tomography images were retrospectively analyzed. The retinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(15 reference statements)
0
9
1
Order By: Relevance
“…In adults with sickle cell disease, Dell'Arti et al [9] reported no association between SCM and age, gender, or genotype; in contrast, Mathew et al [8] reported positive associations with both younger age and HbSS genotype. Others have also reported an association with the HbSS genotype [17,18]. In our study population, there was no clear association between SCM and PSR (Goldberg stages 0, 1, and 2 vs. 3, 4, and 5).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In adults with sickle cell disease, Dell'Arti et al [9] reported no association between SCM and age, gender, or genotype; in contrast, Mathew et al [8] reported positive associations with both younger age and HbSS genotype. Others have also reported an association with the HbSS genotype [17,18]. In our study population, there was no clear association between SCM and PSR (Goldberg stages 0, 1, and 2 vs. 3, 4, and 5).…”
Section: Discussioncontrasting
confidence: 74%
“…Although thinning of the inner nuclear layer is the most obvious feature of SCM on qualitative review of the structural OCT images, Dell’Arti et al [9]reported significant thinning of multiple retinal layers from the ganglion cell layer to the outer nuclear layer in eyes with SCM compared to eyes without SCM. Several authors have described thinning of a range of ETDRS subfields in the eyes of cases with sickle cell disease, especially in those with the HbSS genotype, although the absolute differences appear small [18-20]. This study identified non-significant thinning of the central 1-mm subfield in the eyes with SCM, compared to those without.…”
Section: Discussionmentioning
confidence: 51%
“…To the best of our knowledge, this is the first investigation of central retinal thickness measurements in Jordanian patients with sickle cell disease. Although patients with sickle cell disease may exhibit asymptomatic proliferative retinopathy, 7 we included patients without clinically evident retinopathy in this study to investigate potential tomographic changes during early stages of disease in those eyes. Future studies should examine the progression of those changes over time, their relationships with the stages of overall retinopathy, and the effects of disease-modifying agents and/or bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 75 children, 30 SCA patients (Group 1), and 45 healthy individuals (Group 2), were included in the study. The mean age was 14.11±3.86 (11)(12)(13)(14)(15)(16)(17)(18) in sickle cell anemia patients and 13.15±2.69 (10)(11)(12)(13)(14)(15)(16)(17)(18) in the healthy control group. Of the patients, 56.6% (n=17) of Group 1 and 44.4% (n=20) of Group 2 were male.…”
Section: Resultsmentioning
confidence: 97%
“…11 While homozygous hemoglobin S disease (Hb SS) is associated with more severe clinical symptoms in patients with SCA, Hb SC disease has been reported to be associated with more severe and earlier retinal disease. 2,17 Lim et al 18 stated that patients with the Hb SC genotype were more prone to developing proliferative retinopathy, but macular thinning was observed more in Hb SS patients. More vaso-occlusive events were observed occuring in Hb SS patients; however, it was noted that proliferative retinopathy was paradoxically less developed in these patients.…”
Section: Discussionmentioning
confidence: 99%